Bis(N-sec-butyl-N-n-propyldithio-carbamato- kappa S-2,S `)(1,10-phenanthroline-kappa N-2,N `)zinc(II) - Alzaalouk, A.S.; Baba, I.; Tahir, M.I.M.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent but very similar molecules comprise the asymmetric unit of the title compound, [Zn(C8H16NS2)(2)-(C12H8N2)]. The N2S4 donor set about Zn is defined by two symmetrically chelating dithiocarbamate ligands and a 1,10-phenanthroline ligand. Distortions from the ideal octahedral coordination geometry arise from the restricted bite angles of the ligands. The main feature of the crystal packing is the formation of tetrameric supramolecular aggregates mediated by C-H center dot center dot center dot S interactions. Disorder was found in each of the sec-butyl groups. This was resolved over two positions in each case with the major components of the disorder having site occupancies in the range 0.551 (6)-0.725 (5).